Development of a dynamic wake model accounting for wake advection delays and mesoscale wind transients. Issue 2 (1st May 2022) - Foloppe, B; Munters, W; Buckingham, S; Vandevelde, L; van Beeck, J
Abstract: With tip height often above 200 meters, currently installed wind turbines are increasingly interacting with the atmospheric boundary layer. Therefore, the research intends to develop a new dynamic wake model that considers weather transient inputs. The Flow Redirection and Induction in Steady State (FLORIS) framework has been proven to be a powerful wake modelling tool even though lacking dynamical effects. An extension of the FLORIS framework is presented in order to include wake advection delays between wind turbines, time-varying and spatially heterogeneous wind conditions. The so-called Observation Points (OPs) are generated at the rotor centre location. Following a Lagrangian approach, the OPs are convected downstream, along the wake of the wind turbine, defining the wake centreline. It is during this process that the dynamics of wind turbine wake and background flow field unsteadiness are included. Finally, using the same approach currently implemented for yaw-misalignment wake deflection, the wake is shifted to match the unsteady wake centreline. The developed model is validated against Large Eddy Simulation for unsteady inflow with variable wind turbine control and wake interactions. The new model is applied to a simulation of the Horns Rev wind farm with a sinusoidally time-varying wind inflow direction to show an hysteresis in the wind farm power extraction curve.